An integrative review of how midwives are screening and assessing for trauma in women within perinatal services - Fiona Callanan; Carmel Bradshaw; Teresa Tuohy; Maria Noonan; Sylvia Murphy; Annmarie Grealish (PLoS ONE, 2025)
Introduction There is a growing body of literature on the significance of trauma and abuse in the perinatal period but despite this, trauma exposure and abuse are often not recognised in maternity care settings. Evidence indicates that women experiencing mental distress during the perinatal period are frequently unidentified or inadequately supported. The purpose of this study was to conduct an integrative review on how midwives screen, assess, and respond to women with trauma histories in the perinatal period and to identify the challenges in providing trauma discussions, screening and assessment. Methods This integrative review followed Whittemore and Knafl’s five-stage framework as it facilitates the inclusion of different methodological approaches to experimental research. Five electronic databases (PsycINFO, MEDLINE, CINAHL, ASSIA, and Web of Science), reference and citation lists were systematically searched from inception with no date, language or geographical limiters set owing to a dearth of research in this subject area. This review was performed and reported according to the PRISMA guidelines. The findings were analysed and synthesised using narrative synthesis. Findings Twenty-two studies met the inclusion criteria and were synthesised using narrative synthesis. Four main themes were identified: 1) Midwives difficulties in asking and discussing interpersonal trauma and abuse and their instinctive use of their observations skills to elicit information; 2) Screening tools to elicit history of interpersonal trauma; 3) Midwife’s response to interpersonal discussions; 4) Training on ‘daring to ask the questions’ and Support on ‘what should I do now’. Discussion Our findings demonstrate a deficit in trauma discussion, screening and assessment of trauma within the perinatal care, domestic violence being the exception. Interpersonal trauma is a significant public health concern that if left unrecognized may increase morbidity and mortality in both mothers and newborns. This study makes recommendations for urgent streamlined trauma discussions and specific training and supervision on trauma-informed care for all healthcare professions in their perinatal role using a whole systems approach.